What Hitler knew : the battle for information in Nazi foreign policy - Shore, Zachary (Oxford University Press, 2003)
This is a study of how the climate of fear in Nazi Germany affected Hitler's advisers and shaped the decision making process. It explores the key foreign policy decisions from the Nazi seizure of power up to the hours before the outbreak of World War II.